OPTIMIZING PHYSICAL EDUCATION AND HEALTH ACHIEVEMENT: A COMPREHENSIVE LITERATURE REVIEW - M. Imran Hasanuddin; M. Adam Mappaompo (Adisam Publisher, 2024)
This comprehensive literature review explores the multifaceted dimensions of optimizing Physical Education (PE) and Health Education to enhance student achievement. Delving into the intertwined realms of academia, physical well- being, and holistic development, the review synthesizes existing research, identifies trends, and offers insights for educators, policymakers, and researchers. The rationale behind this exploration lies in the urgency to address sedentary lifestyles and health challenges, aiming to empower students for a future marked by academic excellence and resilient health. The review encompasses diverse aspects, from the correlation between physical activity and cognitive performance to the motivational impact of PE on academic engagement. By examining the interplay between physical and mental aspects, this literature review contributes to the ongoing discourse on fostering well-rounded individuals through optimized PE and Health Achievement.